Cárie dentária em escolares: impacto na qualidade de vida e uso do tratamento restaurador atraumático como solução parcial da demanda - Camilla Aparecida Silva de Oliveira (2015)
The aim of this study was to evaluate the impact of dental caries in the quality of life related to oral health of schoolchildren and examine the possibility of the existing demand solution, using the Atraumatic Restorative Treatment (ART). A cross-sectional study was conducted as a sample of 461 children aged six to 12 years, four public schools in the Regional Pampulha in Belo Horizonte, which were selected for participating in the Healthy Schools Extension Project, linked to theDepartment of Preventive Social Dentistry, School of Dentistry, Federal University of Minas Gerais. All children underwent clinical examination and those six to 10 years, also applied an instrument capable of measuring the quality of life related to oral health. This study will be presented in two papers format. For both, the main independent variable was to dental caries, diagnosed through the DMFT (permanent teeth) and dmft (deciduous teeth). In the first article, we sought to assess the impact of dental caries in the quality of life related to oral health of schoolchildren 6-10 years. To this end, an interviewer applied the Brazilian versionof the Child Perceptions Questionare (CPQ8-10) for all children of this age group, totaling a final sample of 255 individuals. In the comparative analysis to the clinical condition of dental caries were considered two groups: caries-free (component decayed = 0) and caries (decayed component 1). For statistical analysis, we used the Mann Whitney test and Spearman correlation coefficient as a measure of association, considering a significance level of 5% ( = 0.05). There was better quality of life indices for the group of children without caries. As carious dentalnumbers increased, there was a tendency to increase the impact on quality of life. The second article, involved a sample of 461 school and aimed to analyze from the prevalence of dental caries, the possibility of existing demand solution, using the TRA. In this study, the carious lesions without evidence of pulp exposure, without the presence of spontaneous pain or history of pain without fistula or abscess and no exfoliation process were given to the TRA. From then on, there was descriptive analysis through the distribution of frequencies and by calculating the Spearman correlation coefficient found the relationship between the variables number of decayed teeth and number of children likely to have the treatment completed by TRA. It was noted that the extent to which increased the number of decayed teeth per child, decreased the number of individuals who might have completed their treatment only by TRA technique. We conclude that: 1) Children with dental caries in more severe and untreated tend to report high negative impact on their quality of life related to oral health, especially in the emotional wellbeing domain; 2) Most children could be given to the TRA, however, this technique alone does not solve the demand for complete, being necessary to create strategies to facilitate children's access to oral health services.